Diagnostic de l’Etat de Fertilité des Sols Sous Culture Cotonnière Dans les Principaux Bassins de Production de Côte d’Ivoire - Kouadio, Emmanuel N’Goran; Koffi, Emmanuel Kassin; Julien, Kouakou Brou; Messoum, Gustave Francis; Brou, Kouamé; N’guessan, Dominique Brou (European Scientific Journal, ESJ, 2018)
The study was conducted to assess the fertility potential of cotton soils in Côte d’Ivoire. A total of 500 plots of cotton farmers in 5 regions of the cotton basin was selected for soil sampling in the horizon 0-20 cm. The chemical analyzes of soil samples in the laboratory were performed on the following parameters: particle size, pHwater, organic matter, total N, available P, K, Ca, Mg and Cation Exchange Capacity (CEC) of soil. The physical characterization revealed that the studied soils are mainly sandy texture in the surface horizon. This gives them a very low retention capacity. The chemical characterization of soils showed that they have reactions ranging from slightly acid to neutral (6.4 <pH<7). These soils have very low levels of total organic matter, total nitrogen, available phosphorus (in northern, south-central and western regions), calcium, potassium, and low values of cation exchange capacity.